A Clinical Study to Evaluate the Efficacy of Shirovirechana Gana Dravya Siddha Asava Nasya in Dusta Prathishyaya w.s.r to Chronic Sinusitis (International Journal of Ayurveda and Pharma Research, 2022)
The word Prathishyaya indicates recurrent attack and can participate due to minute etiological factors. Prathishyaya can occur as a separate disease entity or symptoms of many systemic diseases or as a complication of other diseases. Prathishyaya if not treated well in early stage and Ahara-Vihara which are harmful for the disease is continued, it leads to a more complicated stage of Prathishyaya i.e., Dusta Prathishyaya. Virechana Nasya which is recommended in Urdwajatrugata Vikaras is indicated in Prathishyaya. For Virechana Nasya- Madhu, Saindhava, Asava, Pitta, Mutra etc drugs has been mentioned by Acharya Vagbhata. So, Asava is prepared by Shirovirechana Gana Dravya as a Prakshepaka Dravyas which possess Katu, Tiktha, Madhura rasa, Laghu and Teekshna Guna, Ushna Veerya, Katu Vipaka and Vata-Kapha shamaka predominantly, which may help in pacify Dusta Prathishyaya. Materials and Methods: A single group study was undertaken in which, 30 patients of Dusta Prathishyaya were randomly selected and were subjected to Asava Nasya - 4 Bindu (2ml) each nostril for 7 days. The patients were assessed with severity of symptoms subjectively and objectively before and after treatment. Data obtained was statistically analysed. Result and Discussion: In overall effect of treatment in Dusta Prathishyaya, out of 30 patients, 3 patients (10%) got moderate improvement, 23 patients (76.6%) got marked improvement and 4 patients (13.33%) got significant improvement. In overall effect of treatment, statistical analysis showed that the mean score which was 6.86 in before treatment was reduced to 4.81 in after treatment and further reduced to 1.86 in follow up, and there is a statistically significant change (P